Penerapan Model Pembelajaran Games untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar pada Materi Menyambut Usia Baligh dalam Mata Pelajaran Pendidikan Agama Islam - Endah Permana Sari; Kasmantoni Kasmantoni (Jurnal Indonesia Pendidikan Profesi Guru, 2026)
Background: The low motivation of elementary school students in learning Islamic Religious Education, particularly on the topic of welcoming puberty, highlights the need for innovative and engaging learning models. Learning activities that are still dominated by lecture-based methods often make students passive and less enthusiastic during the learning process. Objective: This study aimed to analyze the implementation of the games-based learning model in improving students’ learning motivation in Islamic Religious Education. Method: This study employed a classroom action research design conducted at SD Negeri 88 Bengkulu Tengah involving fifth-grade students. Data were collected through observations, tests, documentation, and field notes. The data were analyzed descriptively by examining students’ learning motivation and learning mastery in each cycle. Results: The findings revealed that the implementation of the games-based learning model increased students’ motivation, participation, and enthusiasm during the learning process. Students became more active in discussions, asking questions, collaborating with peers, and responding positively to learning activities. Conclusion: The study concludes that the games-based learning model is effective in creating active, enjoyable, and motivating learning experiences in Islamic Religious Education. Contribution: This research contributes to the development of innovative and student-centered learning models in elementary Islamic education